MODERASI BERAGAMA DAN MULTIKULTURAL DALAM PANDANGAN DAN PENGAJARAN AKADEMISI DI UIN AR-RANIRY DAN UIN ANTASARI - 1M. Hasbi Amiruddin; Munawiyah; Cut Zainab (Kalam: Jurnal Agama dan Sosial Humaniora, 2022)
This article reveals the perspectives of academics from Ar-Raniry State Islamic University and Antasari State Islamic University on religious moderation and multiculturalism. Primary data obtained from the field were collected by direct interview technique with informants from the State Islamic University of ar-Raniry and the State Islamic University of Antasari. Data analysis was carried out with a qualitative approach with descriptive and comparative analysis techniques. Findings in the field show that academics both at UIN Ar-Raniry and at UIN Antasari have attitudes, understandings, and policies that prioritize the values of religious moderation and multiculturalism. On this basis, this article concludes that Islamic Higher Education has great potential and can be relied upon to build religious moderation in a pluralistic and multicultural Indonesia.